2023
DOI: 10.1111/dar.13702
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vaping on uptake and cessation of smoking: Longitudinal analysis in Aotearoa New Zealand adults

Abstract: IntroductionGlobally, the use of vapes, or e‐cigarettes, is increasing. While vaping is less harmful than smoking and may help smokers to quit, there is also the possibility that vaping may lead to smoking. The current study aimed to determine the prevalence of vaping and smoking in Aotearoa New Zealand and explore longitudinal pathways between smoking status and vape use.MethodData related to smoking and vaping status was analysed from Times 10, 11 and 12 across 2018–2020 of the New Zealand Attitudes and Valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…For example, it would be useful to explore the different aspects of sensation seeking including disinhibition, boredom susceptibility, thrill and adventure seeking, and experience seeking using the Sensation Seeking Scale [54, 55], as well as multiple dimensions of impulsivity including negative urgency, premeditation, perseverance, sensation seeking, and positive urgency using the UPPS‐P scale [56, 57] as prior research found that lack of premeditation and greater sensation seeking predicted more e‐cigarette use among e‐cigarette‐using young adults [37]. Finally, more attention needs to be paid to the complex temporal pathways between vaping and smoking over time, including potential gateway effects of vaping on smoking [58] and on alcohol use [59], in addition to common liabilities that may underlie these behaviours [49].…”
Section: Discussionmentioning
confidence: 99%
“…For example, it would be useful to explore the different aspects of sensation seeking including disinhibition, boredom susceptibility, thrill and adventure seeking, and experience seeking using the Sensation Seeking Scale [54, 55], as well as multiple dimensions of impulsivity including negative urgency, premeditation, perseverance, sensation seeking, and positive urgency using the UPPS‐P scale [56, 57] as prior research found that lack of premeditation and greater sensation seeking predicted more e‐cigarette use among e‐cigarette‐using young adults [37]. Finally, more attention needs to be paid to the complex temporal pathways between vaping and smoking over time, including potential gateway effects of vaping on smoking [58] and on alcohol use [59], in addition to common liabilities that may underlie these behaviours [49].…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Dai and Blagev show that longitudinal nicotine exposure with or without advanced disease consequences has adverse neurocognitive consequences [65,66]. Many studies have confirmed a "gateway effect" from early nicotine use, and many pod-based nicotine products, like Juul and disposable e-cigarettes, have high levels of nicotine that result in rapid addiction by users [67][68][69]. E-cigarette use not only results in the dual use of nicotine products but also leads to nicotine and cannabis product use, a practice of growing concern to researchers as cannabis becomes legal in more countries [70,71].…”
Section: Neurological Effectsmentioning
confidence: 99%